Early, precise, and safe clinical evaluation of the pharmacodynamic effects of novel agents in the intact human tumor microenvironment - Gundle, Kenneth R.; Rajasekaran, Karthik; Houlton, Jeffrey; Deutsch, Gary B.; Ow, Thomas J.; Maki, Robert G.; Pang, John; Nathan, Cherie-Ann O.; Clayburgh, Daniel; Newman, Jason G.; Brinkmann, Elyse; Wagner, Michael J.; et al. (Frontiers in Pharmacology, 2024)
Drug development is systemically inefficient. Research and development costs for novel therapeutics average hundreds of millions to billions of dollars, with the overall likelihood of approval estimated to be as low as 6.7% for oncology drugs. Over half of these failures are due to a lack of drug efficacy. This pervasive and repeated low rate of success exemplifies how preclinical models fail to adequately replicate the complexity and heterogeneity of human cancer. Therefore, new methods of evaluation, early in the development trajectory, are essential both to rule-in and rule-out novel agents with more rigor and speed, but also to spare clinical trial patients from the potentially toxic sequelae (high risk) of testing investigational agents that have a low likelihood of producing a response (low benefit). The clinical in vivo oncology (CIVO®) platform was designed to change this drug development paradigm.CIVO precisely delivers microdose quantities of up to 8 drugs or combinations directly into patient tumors 4 to 96 hours prior to planned surgical resection. Resected tissue is then analyzed for responses at each site of intratumoral drug exposure. To date, CIVO has been used safely in 6 clinical trials, including 68 subjects, with 5 investigational and 17 approved agents. Resected tissues were analyzed initially using immunohistochemistry and in situ hybridization assays (115 biomarkers). As technology advanced, the platform was paired with spatial biology analysis platforms, to successfully track anti-neoplastic and immune-modulating activity of the injected agents in the intact tumor microenvironment.Herein we provide a report of the use of CIVO technology in patients, a depiction of the robust analysis methods enabled by this platform, and a description of the operational and regulatory mechanisms used to deploy this approach in synergistic partnership with pharmaceutical partners. We further detail how use of the CIVO platform is a clinically safe and scientifically precise alternative or complement to preclinical efficacy modeling, with outputs that inform, streamline, and de-risk drug development.